Kajian dan Peran Musik dalam Perayaan Paskah di GBI Keluarga Besar Medan Plaza - Alethea Manuela Parrangan; Rithaony Hutajulu; Hubari Gulo (Mahesa Research Center, 2026)
This study examines the role of music in the National Easter Celebration at GBI Keluarga Besar Medan Plaza through a qualititative descriptive approach. The objectives of this study are: (1) to explain the worship order in the National Easter Celebration service; (2) to determine the function of music as a liturgical tool; (3) to determine the musical structure. In examining the role of music in the National Easter Celebration at the GBI Keluarga Besar Medan Plaza, the researcher used a descriptive qualitative approach. When collecting data, the researcher used observation, interview, and documentation methods. The results of the study show that music in the National Easter Celebration service at the GBI Keluarga Besar Medan Plaza has complex functions, including expressive, communicative, normative, symbolic, and integrative. Musical elements are arranged to create a flow of worship that is emotionally and spiritually touching. In conclusion, music in the National Easter Celebration at the GBI Keluarga Besar Medan Plaza is not merely a complement, but becomes a means of uniting congregations from various backgrounds, a medium of spiritual communication, and a vessel for expressing faith that deepens the meaning of worship collectively